Correlation between Endoscopic and Histopathological Findings in Gastric Lesions (Jalalabad Medical Journal, 2025)
Accurate diagnosis of gastric lesions is crucial for early detection and appropriate management. This study aimed to investigate the correlation between endoscopic findings and histopathological diagnoses in gastric lesions among patients at a tertiary care hospital in Bangladesh. This cross-sectional analytical study reviewed hospital records from Jalalabad Ragib-Rabeya Medical College Hospital from January 2023 to December 2023. It included 104 patients diagnosed with gastric lesions who underwent both endoscopic and histopathological examination. Data were collected on patient demographics, endoscopic findings, and histopathological diagnoses. The correlation between endoscopic and histopathological findings was evaluated using appropriate statistical tests. The majority of participants were aged 51-60 years (33.7%), with a higher proportion of males (70.2%). Endoscopic findings included growth-related lesions (69.2%), ulcerative lesions (10.6%), and erosive lesions (20.2%). Histopathological findings revealed malignant tumours (67.3%), chronic inflammatory conditions (22.1%), polypoid lesions (4.8%), and normal findings (5.8%). A significant correlation was observed between endoscopic findings and histopathological diagnosis, with 95.8% of growth-related lesions corresponding to malignant tumours. Additionally, ulcerative lesions were strongly associated with malignant tumours, and erosive lesions correlated with chronic inflammatory conditions. This study highlights a strong correlation between specific endoscopic findings and histopathological diagnoses in gastric lesions, emphasizing the importance of integrated diagnostic approaches for accurate diagnosis and management.Jalalabad Med J 2024; 21 (2); 62-67